A New Method for Determining Appropriate Sites for Growing Perennial Crops - Margarita Mondeshka – Nedyalkova (Bulgarian Journal of Soil Science)
A new quantitative multi-level method for assessing land suitability has been developed, which is intended for evaluation activities for specific goals - mainly when selecting sites for creating new orchards and vineyards, agro-ecological zoning and preparing specific programs/projects. It represents a complex assessment of biophysical conditions (soil, relief and climatic conditions) and is based on the interrelationship "soil - plant - climate", reflecting the biological characteristics of the respective perennial crop and its requirements for the specified conditions. This method suggests possibilities for selecting the areas with the most suitable conditions, where the risks associated with the expected desired quantity and quality of production, the costs of creating and operating the plantations would be minimized. On its basis, an application in GIS can be developed, which allows work automation, as well as creation of thematic maps for the purposes of zoning of perennial plantations and when implementing large investment projects in the field of agriculture. It can also serve as a basis for sustainable land management and sustainable land use planning.